Enhancing volatile fatty acids production from waste activated sludge by a novel cation-exchange resin assistant strategy - Pang, Heliang (2022)
This study developed a novel strategy for enhancing volatile fatty acids production from waste activated sludge by cation-exchange resin assistant anaerobic fermentation. The process condition was optimized by response surface methodology. Considerable sludge disintegration degree (40.9%) and volatile fatty acids yield (4619.6 mg COD/L) were achievable at the proposed process conditions, i.e. cation-exchange resin dosage = 2.05 and 1.78 g/g SS, fermentation time = 4.97 and 6.46 d, and stirring strength = 246.9 and 261.2 rpm, respectively. Grey relational analysis revealed that cation-exchange resin dosage, fermentation time, and stirring strength presented similarly significant effects on sludge disintegration. The reusability tests showed that NaCl solution had the best effect on cation-exchange resin regeneration, and the performance of regenerated resin was comparable with the original resin on volatile fatty acids production. Compared with conventional pretreatment methods, the proposed cation-exchange resin assistant strategy revealed obvious advantages of saved pretreatment agents, easy operation, none chemical residual in sludge and small footprint. Total volatile fatty acids recovery can reach 1.46 × 108 tons chemical oxygen demand annually in terms of China's context, which could offset one third of carbon gap in China's wastewater treatment plants. The proposed cation-exchange resin assistant strategy indeed sheds lights on the direction for WAS treatment in a close alignment with process viability and engineering feasibility.